Ear Prosthesis for Postburn Deformity. (29th April 2018) - Chinnasamy, Alagesan; Gopinath, Vidhya; Jain, Ashish R.
Abstract : Prosthodontics is not just confined to replacement of missing teeth but beyond one's scope. The fabrication of any extraoral maxillofacial prosthesis presents the prosthodontist with several phenomenal challenges. Psychologically, these patients are severely affected either by congenital absence or loss of ear due to trauma or burns. Replacement or reconstruction can be done by surgical or prosthetic approach. However, not all situations are favourable to surgical reconstruction. This article emphasises on the steps in fabrication of ear prosthesis for burn deformity.